Educational data mining - Toh, Jun Hao. (2013)
Mathematics is one of the core subjects which all Secondary School students have to take in order to further on with their tertiary education or qualify for the workforce. With multiple subjects to focus before the examinations, educators and parents are finding the quickest and fastest method to best equip the students to face the examination challenge.